Legal Definitions of Intimate Images in the Age of Sexual Deepfakes and Generative AI - Dunn, Suzie (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2024)
This article explores the evolution of Canadian criminal and civil responses to non-consensual synthetic intimate image creation and distribution. In recent years, the increasing accessibility of this type of technology, sometimes called deepfakes, has led to the proliferation of non-consensually created and distributed synthetic sexual images of both adults and minors. This is a form of image-based sexual abuse that law makers have sought to address through criminal child pornography laws and non-consensual distribution of intimate image provisions, as well as provincial civil intimate image legislation. Depending on the province a person resides in and the age of the person in the image, they may or may not have protection under existing laws. This article reviews the various language used to describe what is considered an intimate image, ranging from definitions seemingly limited to authentic intimate images to altered images and images that falsely present the person in a reasonably convincing manner.